A method for preparing supramolecular adsorption material and its application

The self-assembly of cyclodextrin and amphiphilic organic ligands form supramolecular adsorption materials, which solves the problems of low adsorption capacity and complex preparation of existing adsorption materials, and achieves efficient and low-cost radionuclide adsorption effects, which are suitable for the treatment of radioactive wastewater and other heavy metal wastewater.

CN116272905BActive Publication Date: 2025-03-14CHINA INSTITUTE OF ATOMIC ENERGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310324213.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-29
Publication Date
2025-03-14
Estimated Expiration
2043-03-29

AI Technical Summary

Technical Problem

The existing radionuclide adsorption materials have problems such as low adsorption capacity, slow rate, complex production and high cost, making it difficult to achieve large-scale production and wide application.

Method used

By self-assembling cyclodextrin with amphiphilic organic ligands to form supramolecular adsorption materials, the hydrophobic cavity and hydrogen bond network structure are used to effectively adsorb radioactive ions. The method includes preparing an aqueous cyclodextrin solution, adding a functional guest and stirring at a constant temperature, adding a cyclodextrin solution dropwise and cooling to stand, and finally filtration and washing to obtain a supramolecular adsorption material.

Benefits of technology

It has achieved radionuclide adsorption materials with excellent performance, low cost and easy to produce on a large scale, with high adsorption capacity and short equilibrium time, and is suitable for radioactive wastewater treatment and other heavy metal wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116272905B_ABST
    Figure CN116272905B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a supramolecular adsorption material and its application. Cyclodextrin and an amphiphilic organic ligand are self-assembled to form the supramolecular adsorption material. According to the host-guest recognition function of cyclodextrin, its hydrophobic cavity "wraps" hydrophobic molecules or hydrophobic parts of molecules, and ligands with hydrophobic functional groups of suitable sizes can enter the hydrophobic cavity of cyclodextrin to form a complex. The cyclodextrin supramolecular adsorption material is obtained by cooling at a specific temperature and isothermal crystallization. The preparation process does not involve complex organic reactions and has low cost. The prepared supramolecular adsorption material has good performance, strong expandability and is easy to be mass-produced. The supramolecular adsorption material of the invention can be well dispersed in an aqueous solution, has high adsorption capacity and short equilibrium time, and can be used not only for the treatment of radioactive wastewater, but also for the treatment of wastewater containing heavy metals and precious metals discharged from industries such as electroplating and hydrometallurgy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of radioactive decontamination, and in particular relates to a preparation method of a supramolecular adsorption material and application thereof. Background Art

[0002] In the process of nuclear energy utilization, a large amount of radioactive waste will inevitably be generated, which may enter the natural environment through water bodies and atmospheric circulation, thus posing a serious threat to the ecological environment. The development of efficient radioactive nuclide separation and enrichment technology is of great significance to the sustainable development of nuclear energy and nuclear accident emergency response.

[0003] For the separation and enrichment of radioactive ions in water, people have developed technologies such as precipitation, solvent extraction, adsorption, electrochemical, and reverse osmosis. Among them, the adsorption method has the advantages of simple equipment and operation, small investment, low operating cost, and good treatment effect. Over the past few decades, traditional materials such as natural clay / minerals, activated carbon, silica gel, zeolite, mesoporous carbon / silicon, and ion exchange resins have been developed for the adsorption and separation of radionuclides at home and abroad, as well as new nanomaterials such as carbon nanotubes, graphene, nano zero-valent iron, metal sulfides, layered metal hydroxides (LDH), metal organic frameworks (MOF), covalent organic frameworks (COF), and MXene. However, these materials still have some defects and are difficult to apply in practice. For example, traditional adsorption materials such as natural clay / minerals, silica gel, zeolite, etc. have problems such as low adsorption capacity and slow rate; although new nanomaterials such as carbon nanotubes, graphene, nano zero-valent iron, metal sulfides, layered metal hydroxides (LDH), MOF / COF, etc. have good adsorption effects, their preparation is complex, costly, and difficult to scale up production. Summary of the invention

[0004] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a preparation method and application of a radionuclide adsorption supramolecular adsorption material with excellent performance, low cost and large-scale production.

[0005] To achieve the above-mentioned purpose of the invention, the technical solution adopted by the present invention is as follows: a method for preparing a supramolecular adsorption material, wherein cyclodextrin and amphiphilic organic ligands are self-assembled to form a supramolecular adsorption material.

[0006] Furthermore, the method for preparing the supramolecular adsorption material comprises the following steps:

[0007] (1) preparing a cyclodextrin aqueous solution;

[0008] (2) adding the functional guest into a polar solvent and stirring at a constant temperature to completely dissolve the functional guest to obtain a functional guest solution;

[0009] (3) adding the functional guest solution dropwise into the cyclodextrin solution at a temperature of 10-90° C., stirring for 6-72 hours, cooling to a specific temperature, and then standing at a constant temperature of 0-25° C. for crystallization for 6-72 hours. After the crystallization is completed, filtering and washing to obtain the cyclodextrin supramolecular adsorption material.

[0010] Furthermore, in the step (1), cyclodextrin is added into water and stirred at a constant temperature of 60-95° C. until it is completely dissolved, thereby obtaining an aqueous solution of cyclodextrin.

[0011] Furthermore, in the step (1), the cyclodextrin is one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, and its mass concentration is 5 to 30 wt%.

[0012] Furthermore, in the step (2), the functional object is one of tributyl phosphate, triisoamyl phosphate, octyl(phenyl)-N,N-diisobutylcarbamoylmethylphosphine oxide (CMPO), benzylaminoxime, benzoic acid, terephthalic acid, biphenyldicarboxylic acid, etc.; the polar solvent is one of water, ethanol, ethylene glycol, propanol, propylene glycol, glycerol, acetonitrile, DMF, DMSO and the like.

[0013] Furthermore, in the step (2), the mass concentration of the functional guest solution is 10-60wt%; and the dissolution temperature is 20-90°C.

[0014] Furthermore, in the step (3), the molar ratio of cyclodextrin / functional guest in the cyclodextrin solution and the functional guest solution is 1:0.5-5.

[0015] Furthermore, in the step (3), the functional guest solution is added dropwise into the cyclodextrin solution at a temperature of 50 to 80° C., stirred for 12 to 36 hours, cooled to a specific temperature, and then allowed to stand at a constant temperature of 0 to 10° C. for crystallization for 12 to 48 hours. After the crystallization is completed, the cyclodextrin supramolecular adsorption material is filtered and washed to obtain the cyclodextrin supramolecular adsorption material.

[0016] The present invention also provides application of the supramolecular adsorption material. The cyclodextrin supramolecular adsorption material is used for radioactive wastewater treatment and adsorption of radioactive ions.

[0017] Furthermore, the application of the supramolecular adsorption material is to add one or more cyclodextrin supramolecular adsorption materials into radioactive waste liquid to adsorb and separate radioactive ions, the adsorption time is 20 to 720 minutes, the concentration of the cyclodextrin supramolecular adsorption material is 0.1 to 10 g / L, the pH of the radioactive waste liquid is 1 to 13, and the adsorption temperature is 15 to 40°C.

[0018] The beneficial effect brought about by the technical solution of the present invention is that the present invention provides a method for preparing a supramolecular adsorption material, according to the host-guest recognition effect of cyclodextrin, its hydrophobic cavity "wraps" hydrophobic molecules or hydrophobic parts of molecules, and ligands with hydrophobic functional groups of appropriate size can enter the hydrophobic cavity of cyclodextrin to form a complex; cooling at a specific temperature and constant temperature crystallization to obtain the cyclodextrin supramolecular adsorption material; the preparation method of the present invention does not involve complex organic reactions, the process is simple, the cost is low, the performance is good, the scalability is strong, and it is easy to mass produce; the supramolecular adsorption material of the present invention can be well dispersed in an aqueous solution, has a high adsorption capacity and a short equilibrium time, and can be used not only in the treatment of radioactive wastewater, but also can be widely used in the treatment of heavy metal and precious metal wastewater discharged from industries such as electroplating and hydrometallurgy. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope image of the TBP@β-cyclodextrin supramolecular adsorption material prepared in Example 2 of the present invention;

[0020] Figure 2 This is a scanning electron microscope image of the CMPO@β-cyclodextrin supramolecular adsorption material prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0021] The present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0022] Embodiment 1

[0023] The embodiment of the present invention provides a method for preparing a supramolecular adsorption material, wherein cyclodextrin and an amphiphilic organic ligand are self-assembled to form a supramolecular adsorption material. According to the embodiment of the present invention, cyclodextrin forms an "inclusion compound" through the interaction between the hydrophilic and hydrophobic effects and the guest molecules, and the solubility of the cyclodextrin inclusion compound decreases during the cooling process, and crystals are gradually precipitated, that is, the cyclodextrin supramolecular adsorption material prepared by the embodiment of the present invention.

[0024] Under the condition temperature of the embodiment of the present invention, the hydroxyl groups on the outer wall of the cyclodextrin inclusion complex form a three-dimensional ordered hydrogen bond network assembly through hydrogen bond interactions. The presence of a large number of hydrogen bonds makes it difficult to dissolve again; and the hydrophobic guest molecules in the cyclodextrin cavity can form hydrogen bonds with the hydroxyl groups at the cyclodextrin ports, further expanding the hydrogen bond network, making the three-dimensional hydrogen bond network of the entire supramolecular system more complex and stable; the introduction of hydrophobic guest molecules reduces the solubility of cyclodextrin. Therefore, during the water dissolution and cooling process, the cyclodextrin inclusion complex forms a water-insoluble cyclodextrin inclusion complex supramolecular assembly by forming a strong hydrogen bond network, that is, the supramolecular adsorption material prepared by the embodiment of the present invention.

[0025] Preferably, the method for preparing the supramolecular adsorption material comprises the following steps:

[0026] (1) preparing a cyclodextrin aqueous solution;

[0027] (2) adding the functional guest into a polar solvent and stirring at a constant temperature to completely dissolve the functional guest to obtain a functional guest solution;

[0028] (3) adding the functional guest solution dropwise into the cyclodextrin solution at a temperature of 10 to 90° C., stirring for 6 to 72 hours, cooling to a specific temperature, and then standing at a constant temperature of 0 to 25° C. for crystallization for 6 to 72 hours. After the crystallization is completed, filtering and washing to obtain the cyclodextrin supramolecular adsorption material.

[0029] In the embodiment of the present invention, a functional guest is added to a cyclodextrin solution, stirred and then cooled to 0-25°C. Hydrogen bonds can be well formed below 25°C. In this temperature range, the inclusion compound can be guaranteed to have a certain migration rate and can diffuse and migrate well to participate in crystallization. At the same time, the inclusion compound has a certain solubility at this temperature, and can make the crystal structure more perfect and the particles larger through the "dissolution-crystallization" equilibrium.

[0030] Preferably, in step (1), cyclodextrin is added into water and stirred at a constant temperature of 60 to 95° C. until it is completely dissolved, thereby obtaining an aqueous solution of cyclodextrin.

[0031] Preferably, in step (1), the cyclodextrin is one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, and its mass concentration is 5 to 30 wt%.

[0032] Preferably, in the step (2), the functional object is one of tributyl phosphate, triisoamyl phosphate, octyl(phenyl)-N,N-diisobutylcarbamoylmethylphosphine oxide (CMPO), benzylaminoxime, benzoic acid, terephthalic acid, biphenyldicarboxylic acid, etc.; the polar solvent is one of water, ethanol, ethylene glycol, propanol, propylene glycol, glycerol, acetonitrile, DMF, DMSO and the like.

[0033] Preferably, in the step (2), the mass concentration of the functional guest solution is 10-60 wt %; and the dissolution temperature is 20-90°C.

[0034] Preferably, in step (3), the molar ratio of cyclodextrin / functional guest in the cyclodextrin solution and the functional guest solution is 1:0.5-5.

[0035] Preferably, in the step (3), the functional guest solution is added dropwise into the cyclodextrin solution at a temperature of 50 to 80°C, stirred for 12 to 36 hours, cooled to a specific temperature, and then allowed to stand at a constant temperature of 0 to 10°C for crystallization for 12 to 48 hours. After the crystallization is completed, the cyclodextrin supramolecular adsorption material is filtered and washed to obtain the cyclodextrin supramolecular adsorption material.

[0036] The embodiment of the present invention also provides the application of the supramolecular adsorption material. The cyclodextrin supramolecular adsorption material is used for radioactive wastewater treatment and adsorption of radioactive ions.

[0037] Preferably, the application of the supramolecular adsorption material is to add one or more cyclodextrin supramolecular adsorption materials into radioactive waste liquid to carry out adsorption and separation of radioactive ions, the adsorption time is 20 to 720 minutes, the concentration of the cyclodextrin supramolecular adsorption material is 0.1 to 10 g / L, the pH of the radioactive waste liquid is 1 to 13, and the adsorption temperature is 15 to 40°C.

[0038] Preferably, the radioactive waste liquid is a liquid containing one or more of actinides such as Th, U, Np, Pu, Am, Cf, lanthanides such as Ce, Pr, Nd, Eu, Gd, and elements such as Zr, Pd, Sr, Cs, etc.

[0039] Preferably, the adsorption amount Q of radioactive ions in the radioactive waste liquid is calculated by formula (1); the removal rate R of radioactive ions is calculated by formula (2);

[0040]

[0041]

[0042] Where C0 is the initial concentration of radioactive ions, C e is the adsorption equilibrium concentration of radioactive ions, in mg / L; m is the mass of the adsorbent material, in g; V is the volume of the radioactive liquid, in L.

[0043] Embodiment 2

[0044] The supramolecular adsorption material was prepared by the method of Example 1 of the present invention, 20 g of β-cyclodextrin was accurately weighed and added to 100 mL of water, and magnetically stirred at a constant temperature of 90°C. After it was completely dissolved, 14.1 g of TBP was added and stirring was continued for 12 h; it was naturally cooled to room temperature, transferred to a 4°C refrigerator and allowed to stand for 12 h; the precipitated solid was centrifuged and washed with water 3 times, and vacuum dried at 60°C to obtain 6.7 g of white crystals, which were cyclodextrin supramolecular adsorption materials.

[0045] See attached Figure 1 The TBP@β-CD inclusion complex is an irregular rhombohedron with a particle size of 1-10 μm and a well-developed exposed crystal face, indicating that the supramolecular adsorption material prepared by the method of the embodiment of the present invention forms a three-dimensional ordered crystal structure.

[0046] Take 10 mg of the cyclodextrin supramolecular adsorption material, add it to 10 mL of 100 mg / L Eu(NO3)3 solution, pH = 5.5, stir at 30°C for 6 hours, take the supernatant and filter it, and determine its concentration by ICP-OES. The above formula (1) is used to calculate that the adsorption amount of Eu by the cyclodextrin supramolecular adsorption material prepared in this embodiment of the present invention is 82.6 mg / g.

[0047] The rest is the same as in the first embodiment.

[0048] Embodiment 3

[0049] The supramolecular adsorption material was prepared by the method of Example 1 of the present invention, 5 g of β-cyclodextrin was accurately weighed and added to 95 mL of water, and magnetically stirred at a constant temperature of 80°C to completely dissolve it; 1.81 g of CMPO was weighed and added to 10 mL of DMF at 60°C to make a solution; the CMPO-DMF solution was added dropwise to the cyclodextrin aqueous solution within 10 minutes, and the solution was stirred at a constant temperature of 80°C for 24 hours; the solution was naturally cooled to room temperature, transferred to a 15°C water bath and allowed to stand for 12 hours; the precipitated solid was centrifuged and washed with water 3 times, and vacuum dried at 60°C to obtain 4.3 g of a white solid, which was a cyclodextrin supramolecular adsorption material.

[0050] The rest is the same as in the first embodiment.

[0051] See attached Figure 2 The CMPO@β-CD inclusion compound particles are rhombohedrons with a width of 0.5-1 μm and a length of 1-3 μm, and their crystal faces are well developed, indicating that the supramolecular adsorption material prepared by the method of the embodiment of the present invention has a high degree of crystallinity.

[0052] Embodiment 4

[0053] The supramolecular adsorption material was prepared by the method of Example 1 of the present invention, 10 g of α-cyclodextrin was accurately weighed and added to 90 mL of water, and magnetically stirred at a constant temperature of 50°C. After it was completely dissolved, 1.4 g of benzylaminoxime was weighed and added to 10 mL of 60°C ethanol to make a solution, and the benzylaminoxime-ethanol solution was added dropwise to the cyclodextrin aqueous solution within 15 minutes, and the mixture was stirred at a constant temperature of 50°C for 24 hours; stirring was continued for 72 hours; naturally cooled to room temperature, transferred to a 4°C refrigerator and allowed to stand for 12 hours; the precipitated solid was filtered and washed with water 3 times, and vacuum dried at 60°C to obtain 7.3 g of a white solid, which was a cyclodextrin supramolecular adsorption material.

[0054] The rest is the same as in the first embodiment.

[0055] Embodiment 5

[0056] The supramolecular adsorption material was prepared by the method of Example 1 of the present invention. 10 g of β-cyclodextrin was accurately weighed and added to 90 mL of water. The water was magnetically stirred at a constant temperature of 80° C. After it was completely dissolved, 1.61 g of terephthalic acid was weighed and added to 20 mL of 60° C. ethanol to make a solution. The terephthalic acid-ethanol solution was added dropwise to the cyclodextrin aqueous solution within 20 min. The solution was stirred at a constant temperature of 80° C. for 10 h. The solution was naturally cooled to room temperature, transferred to a 4° C. refrigerator and allowed to stand for 12 h. The precipitated solid was filtered and washed with water 3 times. The solution was vacuum dried at 60° C. to obtain 10.45 g of a white solid, which was a cyclodextrin supramolecular adsorption material.

[0057] Weigh 100 mg of Example 3 and 100 mg of the cyclodextrin supramolecular adsorption material prepared in this example, add 10 mL of a radioactive waste liquid with an acidity of 0.35 M HNO3, stir at 30°C for 2 h, take the supernatant and filter it, and use ICP-MS to determine the concentration of each ion, and calculate the removal rate and distribution coefficient of different ions. The M element and the calculation results are shown in Table 1.

[0058] Table 1 The removal effect of cyclodextrin supramolecular adsorption materials on radioactive ions in radioactive waste liquid

[0059]

[0060]

[0061] It can be seen from the data in the table that the cyclodextrin supramolecular adsorption material prepared in the embodiment of the present invention can effectively remove actinides and lanthanides in radioactive waste liquid.

[0062] The rest is the same as in the first embodiment.

[0063] Embodiment 6

[0064] The supramolecular adsorption material was prepared by the method of Example 1 of the present invention. 10 g of γ-cyclodextrin was accurately weighed and added to 90 mL of water. The water was magnetically stirred at a constant temperature of 90° C. After it was completely dissolved, 2.25 g of biphenyl dicarboxylic acid was weighed and added to 10 mL of 60° C. ethanol to make a solution. The biphenyl dicarboxylic acid-ethanol solution was added dropwise to the cyclodextrin aqueous solution within 10 minutes. The solution was stirred at a constant temperature of 90° C. for 10 hours. The solution was naturally cooled to room temperature, transferred to a 1° C. refrigerator and allowed to stand for 48 hours. The precipitated solid was filtered and washed with water 3 times. The solution was vacuum dried at 60° C. to obtain 7.2 g of a white solid, which was a cyclodextrin supramolecular adsorption material.

[0065] Weigh 70 mg of Example 3, 70 mg of Example 5 and 70 mg of the cyclodextrin supramolecular adsorption material prepared in this example, add them together to 10 mL of simulated radioactive waste liquid with an acidity of 0.1 M HNO3, stir at 30°C for 2 h, take the supernatant and filter it, and use ICP-OES to determine the concentration of each ion, and calculate the removal rate and distribution coefficient of different ions. The M element composition and the calculation results are shown in Table 2.

[0066] Table 2 Cation composition and removal rate of simulated radioactive waste liquid with acidity of 0.1M HNO3

[0067] ion <![CDATA[La 3+ ]]> <![CDATA[Ce 3+ ]]> <![CDATA[Nd 3+ ]]> <![CDATA[Sm 3+ ]]> <![CDATA[Eu 3+ ]]> <![CDATA[Ba 2+ ]]> <![CDATA[Mo 2+ ]]> <![CDATA[Sr 2+ ]]> <![CDATA[Zr 4+ ]]> <![CDATA[Ag + ]]> Content mg / L 4.75 5.72 1.24 0.07 0.1 6.5 83.5 10.2 0.1 0.7 Removal rate % 87.9 91.6 97.1 — 98.9 42.6 64.8 26.3 97.8 —

[0068] Note: “—” is lower than the detection limit of the instrument, indicating that the removal rate is very high.

[0069] It can be seen from the data in the table that the cyclodextrin supramolecular adsorption material prepared in the embodiment of the present invention can effectively remove lanthanide and transition metal elements in radioactive waste liquid.

[0070] The rest is the same as in the first embodiment.

[0071] Embodiment 7

[0072] The supramolecular adsorption material was prepared by the method of Example 1 of the present invention. 10 g of β-cyclodextrin was accurately weighed and added to 90 mL of water. The mixture was magnetically stirred at a constant temperature of 60°C. After it was completely dissolved, 12.1 g of TBP was added and stirring was continued for 24 h. Then, the mixture was naturally cooled to room temperature and transferred to a 4°C refrigerator and allowed to stand for 72 h. Finally, the precipitated solid was centrifuged and washed with water three times, and vacuum dried at 60°C to obtain 11.7 g of white crystals.

[0073] Weigh 5 mg of each of the cyclodextrin supramolecular adsorption materials prepared in Examples 2 to 7, add them to 5 mL of a 100 mg / L UO2(NO3)2 solution with a pH of 6, stir at 25°C for 5 h, filter the supernatant, determine its concentration using ICP-OES, and calculate the adsorption capacity of U using Formula 1. The results are shown in Table 3.

[0074] Table 3 Adsorption performance of cyclodextrin supramolecular adsorption materials prepared in Examples 2 to 7 for U

[0075] Adsorption material Adsorption capacity mg / g Embodiment 2 65.6 Embodiment 3 65.3 Embodiment 4 78.6 Embodiment 5 72.1 Embodiment 6 63.3 Embodiment 7 76.9

[0076] It can be seen from the data in the table that the cyclodextrin supramolecular adsorption material prepared in the embodiment of the present invention has good adsorption performance for U.

[0077] 10 mg of the cyclodextrin supramolecular adsorption material prepared in Examples 2 to 7 was weighed separately and added to 10 mL of 200 mg / L Th(NO3)4 solution with a pH value of 4.5. The solution was stirred at 25°C for 3 h. The supernatant was filtered and its concentration was determined by ICP-OES. The adsorption capacity and removal rate of Th were calculated using Formulas 1 and 2, respectively. The results are shown in Table 4.

[0078] Table 4 Adsorption performance of Th by cyclodextrin supramolecular adsorption materials prepared in Examples 2 to 7

[0079]

[0080]

[0081] It can be seen from the data in the table that the cyclodextrin supramolecular adsorption material prepared in the embodiment of the present invention has good Th adsorption capacity and high removal rate.

[0082] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. An application of a supramolecular adsorption material, characterized in that: One or more cyclodextrin supramolecular adsorption materials are added to radioactive waste liquid to perform adsorption and separation of radioactive ions, the adsorption time is 20-720 min, the concentration of the cyclodextrin supramolecular adsorption material is 0.1-10 g / L, the pH of the radioactive waste liquid is 1-13, and the adsorption temperature is 15-40°C. The preparation method of the supramolecular adsorption material comprises the following steps: (1) preparing a cyclodextrin aqueous solution with a mass concentration of 5-30 wt%; (2) adding a functional guest to a polar solvent and stirring at a constant temperature to dissolve it completely to obtain a functional guest solution; the functional guest is one of tributyl phosphate, triisoamyl phosphate, octyl(phenyl)-N,N-diisobutylcarbamoylmethylphosphine oxide (CMPO), benzylaminoxime, benzoic acid, terephthalic acid, and diphenyl dicarboxylic acid; the polar solvent is one of water, ethanol, ethylene glycol, propanol, propylene glycol, glycerol, acetonitrile, DMF, and DMSO; (3) Adding the functional guest solution dropwise into the cyclodextrin solution at a temperature of 10-90°C, stirring for 6-72 hours, cooling to a specific temperature, and then standing at a constant temperature of 0-25°C for crystallization for 6-72 hours. After the crystallization is completed, filtering and washing to obtain the cyclodextrin supramolecular adsorption material.

2. The use of a supramolecular adsorption material according to claim 1, characterized in that: In step (1) of the method for preparing the supramolecular adsorption material, cyclodextrin is added into water and stirred at a constant temperature of 60-95° C. until it is completely dissolved, thereby obtaining an aqueous solution of cyclodextrin.

3. The use of a supramolecular adsorption material according to claim 1, characterized in that: In step (1) of the method for preparing the supramolecular adsorption material, the cyclodextrin is one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin.

4. The use of a supramolecular adsorption material according to claim 1, characterized in that: In step (2) of the method for preparing the supramolecular adsorption material, the mass concentration of the functional guest solution is 10-60 wt %; and the dissolution temperature is 20-90° C.

5. The use of a supramolecular adsorption material according to claim 1, characterized in that: In step (3) of the method for preparing the supramolecular adsorption material, the molar ratio of cyclodextrin / functional guest in the cyclodextrin solution and the functional guest solution is 1:0.5-5.

6. The use of a supramolecular adsorption material according to claim 1, characterized in that: In step (3) of the method for preparing the supramolecular adsorption material, the functional guest solution is added dropwise into the cyclodextrin solution at a temperature of 50-80°C, stirred for 12-36 hours, cooled to a specific temperature, and then allowed to stand at a constant temperature of 0-10°C for crystallization for 12-48 hours. After the crystallization is completed, the cyclodextrin supramolecular adsorption material is filtered and washed to obtain the cyclodextrin supramolecular adsorption material.

Citation Information

Patent Citations

  • Beta-cyclodextrin-benzoic acid clathrate compound and preparation method thereof

    CN106543296A

  • Europium adsorbent based on cyclodextrin polycarboxylic acid polymer and application method of adsorbent

    CN112934202A